2018
DOI: 10.1021/acs.estlett.8b00319
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria as an Electron Shuttle for Sulfide Oxidation

Abstract: Biological desulfurization under haloalkaliphilic conditions is a widely applied process, in which haloalkalophilic sulfide-oxidizing bacteria (SOB) oxidize dissolved sulfide with oxygen as the final electron acceptor. We show that these SOB can shuttle electrons from sulfide to an electrode, producing electricity. Reactor solutions from two different biodesulfurization installations were used, containing different SOB communities; 0.2 mM sulfide was added to the reactor solutions with SOB in absence of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 11 publications
(21 reference statements)
3
38
1
Order By: Relevance
“…Based on the difference between calculated and measured HS – concentrations, the specific HS – uptake in the anaerobic bioreactor was calculated (i.e., mg HS – per mg N of biomass (see Figure 2C). The specific HS – uptake in the anaerobic bioreactor was between 0.24 and 3.4 mg S/mg N, whereas ter Heijne 16 observed an HS – uptake of 0.22 mg S/mg N under anaerobic conditions in a batch experiment. The HS – uptake will be further discussed in Section 3.3.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the difference between calculated and measured HS – concentrations, the specific HS – uptake in the anaerobic bioreactor was calculated (i.e., mg HS – per mg N of biomass (see Figure 2C). The specific HS – uptake in the anaerobic bioreactor was between 0.24 and 3.4 mg S/mg N, whereas ter Heijne 16 observed an HS – uptake of 0.22 mg S/mg N under anaerobic conditions in a batch experiment. The HS – uptake will be further discussed in Section 3.3.…”
Section: Resultssupporting
confidence: 89%
“…Recently, it has been shown that SOB taken from biodesulfurization systems, are capable of HS – uptake in the absence of oxygen. 16 Hence, it can be hypothesized that when SOB are exposed to elevated HS – levels in the anaerobic bioreactor, HS – concentration will be decreased and the HS – concentration in the influent of the aerobic bioreactor is lower. As a result, chemical oxidation rates in the aerated bioreactor will decrease and S 2 O 3 2– formation will be lower.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the global recovery of the current reached 27% ± 4%, which means that a high amount of current was probably lost in parasitic reactions in the reductive reactor, such as in the hydrogen shortcut between the cathode and the anode or in the presence of bioelectrochemical oxidation of the ammonium nitrogen and the sulfide present in the mineral medium. In more detail, in the inner counterelectrode part of the reductive reactor, both ammonium nitrogen and sulfide could be bioelectrochemically oxidized into nitrate and elemental sulfur, respectively, as has been reported in the literature [42][43][44]. Even though the anion determination did not show the presence of nitrate or sulfide removal, the presence of bioelectrochemical oxidation cannot be excluded due to the possibility of an oxidation/reduction electron loop; therefore, the contribution of each mechanism could not be quantified in the electron balance of the process.…”
Section: Continuous Flow Operation Of the Sequential Oxidative/reductmentioning
confidence: 63%
“…Microorganism could transfer the electrons to the humic substances, then the reduces humic substances can rapidly reduces iron (III) oxides (Roden et al, 2010). The self-charge and storage capability could also be quinone based compounds (ter Heijne et al, 2018). The anode potential drop was much higher with pure marine sediment bioanodes (more than 300 mV) than the AC based electrode.…”
Section: Resultsmentioning
confidence: 99%